A 3-D binder-free nanoporous anode for a safe and stable charging of lithium ion batteries. (September 2017) - Chen, Yijun; Wang, Yunsong; Yousaf, Muhammad; Ma, Zhimin; Zou, Mingchu; Cao, Anyuan; Han, Ray P.S.
Highlights: In situ growth of T-Nb2 O5 nanocrystals in CNT sponge for a safe binder-free anode. 3-D nanoporous structural network enhances rate capability and cycling stability. Voltage window of hybrid anode varies from 1 to 3 V to prevent SEI formation. Binder-free anode has high retention rates after 1000 cycles. Graphical abstract: T-Nb2 O5 nanocrystals are in situ grown in CNT sponges and serve as binder-free, safe and stable lithium ion battery anodes. Abstract: Nb2 O5 is considered as a promising safe anode material for lithium ion batteries due to its high operating voltage (>1 V) that prevents the formation of the solid electrolyte interface; however, the low intrinsic conductivity and pulverization during long-term charge/discharge process limit its practical use. To address these twin adverse issues, we report on the development of a 3-D nanoporous anode that is binder-free by uniformly depositing in-situ orthorhombic Nb2 O5 nanocrystals inside the highly conductive carbon nanotube sponge. The end result is a novel 3-D hybrid anode that delivers a maximum reversible capacity of 230 mAh g −1 within a voltage window of 1.0–3.0 V versus Li/Li + . At a current density of 1 A g −1 (5C), the hybrid anode exhibits a specific capacity of ∼150 mAh g −1 with an 82% retention after 1000 charge/discharge cycles, which represents an improved cycling stability and rate capability compared to conventional powder anodes.